PERAN DIGITAL MARKETING DALAM EKSISTENSI BISNIS KULINER SEBLAK JELETET MURNI - Nadya, Nadya (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
Technological developments have significantly changed the way how a business works, especially the culinary business named Seblak Jeletet Murni, that has located in Jakarta. This business is still relatively new, but consumers continue moldy and this spicy culinary product sales have been continue to increase. This phenomenon is a result of business which has entered the digital era in social media. Marketing of this product is not done intensively by the owner of this business, but consumers who moved to market virally in social media, especially social media video youtube. In this article the author analyzed descriptively about consumer behavior in digital marketing that has affected the sales of the culinary products. The analyzes were performed with case studies and associated in the literature on consumer behavior and digital marketing strategies. This article aims to describe the behavior of consumers in the digital age so that it can be input in determining the marketing strategy culinary efforts forward and be used for thought on the future of consumer research. Keywords: Digital Marketing, Social Media, Consumer Behavior